Motif Masyarakat Non Muslim Menjadi Nasabah Gadai Pada Bank Syariah Indonesia Cabang Kota Jambi Menurut Perspektif Ekonomi Islam - Suci Martha Liany; Arsa Arsa; Refky Fielnanda (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
The background to this thesis is that apart from Muslim customers, there are also non-Muslim customers who are gold pawning customers at the Pekanbaru branch of Bank Syariah Mandiri. The aim of this research is to find out the motives of non-Muslim communities for using gold pawning financing services at Bank Syariah Indonesia Jambi Branch Office and to find out how Islamic economics views the motives of non-Muslim communities for using gold pawning financing services at Bank Syariah Indonesia Jambi Branch Offices. The population in this study was 4 non-Muslim customers who used the gold pawn financing services of Bank Syariah Indonesia, Jambi City Branch. This research is field research or what is known as field research. The location of this research is Bank Syariah Indonesia, Jambi City. The sample in this research was all non-Muslim customers, namely 4 people who used gold pawning financing services at Bank Syariah Indonesia, Jambi City. After the author conducted research, it can be concluded that the motive for non-Muslim people to become gold pawning customers at Bank Syariah Indonesia Jambi City Branch is because non-Muslim customers need capital, such as to sell in markets. Some of the motives used by non-Muslim customers are personal motives, cultural motives, religious motives, stimuli, Islamic economic views on the motives of non-Muslim communities for using gold pawn financing services at the Pekanbaru branch of Bank Syariah Mandiri in accordance with the rules of Allah SWT, leading to the achievement of goodness, prosperity, helping humans to achieve success.